Rudolf Puspa's Communication Style in the Teater Keliling - Septian Nurcahyo (Universitas Muhammadiyah Enrekang, 2024)
One of the keys to the success of a theatre performance is the communication pattern between the director and the crews. Any organization (regardless of its form) can run well if the conversations among its crews and leaders function smoothly, especially if the organization consists of members with a significant age difference. To be precise, age differences can sometimes become barriers in communication or the process of conveying messages. This article aims to provide an analytical exposition on Rudolf Puspa's leadership style through communication management in managing the Teater Keliling. This type of research is qualitative research using a qualitative descriptive approach. The author will research natural object conditions, where the research subject is a key factor. All data obtained are in the form of interviews, documentation, field notes, and observations. In addressing the age gap in Teater Keliling, Rudolf Puspa strives to learn several things, one of which is to study topics that attract the attention of today’s youth and appoint his own child as a producer. Thus, his child can convey his instructions more simply and easily understood to the crew with the same age. He is a leader with a democratic style. This can also be seen from how he is willing to listen, open up for discussions together, and accept input from Teater Keliling crews who are much younger than him. As the “Father” of Teater Keliling, he realizes that he must apply an adaptive attitude to maintain the longevity of the community he loves. He does all this in the name of the theatrical art that has become one with him.